Effects of goal-setting skills on students'academic performance in english language in Enugu Nigeria - Abe Iyabo Idowu; Ilogu Guy Chibuzoh; Madueke L I (Springer, 2014)
The study investigated the effectiveness of goal-setting skills among Senior Secondary II students' academic performance in English language in Enugu Metropolis, Enugu state, Nigeria. Quasi-experimental pre-test, post- test control group design was adopted for the study. The initial sample was 147 participants (male and female) Senior Secondary School II students drawn from two public schools in Enugu zone of Enugu Metropolis. The final sample for the intervention consisted of 80 participants. This sample satisfied the condition for selection from the baseline data. Two research hypotheses were formulated and tested at 0.05 level of significance. Data generated were analyzed using the mean, standard deviation and t-test statistical method. The findings showed that performance in English language was enhanced among participants exposed to goal-setting intervention compared to those in the control group. The study also showed that there is a significant gender difference in students' performance with female participants recording a higher mean score than males. Parental level of education was also found to be related to performance in English Language. Based on the findings, goal-setting intervention was recommended as a strategy to enhancing students' academic performance particularly in English Language.